Correlation of Serum Cardiac Markers with Acute Decompensating Events in Liver Cirrhosis - Li, Miaomiao; Guo, Zeqi; Zhang, Dan; Xu, Xiangbo; Romeiro, Fernando Gomes [UNESP]; Mancuso, Andrea; Zhang, Jingqiao; Feng, Ruirui; Zhou, Xinmiao; Hong, Cen; Qi, Xingshun (Hindawi, 2020)
Background and Aim. Liver cirrhosis is often accompanied by insidious cardiac dysfunction. This retrospective cross-sectional study is aimed at exploring the correlation between serum cardiac markers and decompensating events in liver cirrhosis. Methods. Cirrhotic patients who were consecutively hospitalized between January 2016 and March 2019 were screened. Serum cardiac biomarkers at admission, including N-Terminal pro-B-type natriuretic peptide (NT-pro BNP), high-sensitivity cardiac troponin T (hs-cTnT), creatine kinase (CK), creatine kinase MB (CK-MB), and lactate dehydrogenase (LDH), were collected. Acute decompensating events at admission, primarily including ascites, acute gastrointestinal hemorrhage, and acute-on-chronic liver failure (ACLF), were recorded. Results. The NT-pro BNP level was significantly higher in cirrhotic patients with acute decompensating events than in those without any decompensating events (median: 140.75 pg/mL versus 41.86 pg/mL, P<0.001). The NT-pro BNP level significantly correlated with ascites, acute gastrointestinal hemorrhage, and ACLF. The hs-cTnT level was significantly higher in cirrhotic patients with acute decompensating events than in those without decompensating events (median: 0.008 ng/mL versus 0.006 ng/mL, P=0.007). The hs-cTnT level significantly correlated with acute gastrointestinal hemorrhage, but not ascites or ACLF. LDH (185.0 U/L versus 173.5 U/L, P=0.281), CK (71 U/L versus 84 U/L, P=0.157), and CK-MB (29.5 U/L versus 33.0 U/L, P=0.604) levels were not significantly different between cirrhotic patients with and without acute decompensating events. Conclusion. The elevated NT-pro BNP level seems to be closely related to the development of acute decompensating events in liver cirrhosis.